On computing of VDR rapid filters control system - Dąbrowski, Wojciech (Instal, 2020)
A simple and accurate method of solving the set of equations describing Variable Declining Rate Filters in a bank was described, based on the literature, including among the others the earlier papers of the author. Only the mathe matical model developed by Di Bernardo was considered, as the most practical from the engineering point of view.